Thermal analysis in oxidative and pyrolysis conditions of alkaline earth metals picolinates using the techniques: TG-DSC, DSC, MWTA, HSM and EGA (TG-DSC-FTIR and HSM-MS) - Nascimento, A. L.C.S. [UNESP] (2018)
Synthesis, characterization, thermal stability and pyrolysis of some alkaline earth picolinates M(C6H5NO2)2⋅nH2O (where M = Mg(II), Ca(II), Sr(II) and Ba(II) and n = di (Mg), mono (Ca), hemi three (Sr) hydrated) were investigated using a range of techniques including simultaneous thermogravimetry and differential scanning calorimetry (TG–DSC), evolved gas analysis (EGA), differential scanning calorimetry (DSC), Hot-Stage microscopy (HSM), powder X-ray diffractometry (PXRD), complexometry with EDTA and elemental analysis (EA). The TG-DSC curves show that the hydrated compounds dehydrate in a single step of mass loss and the thermal stability of the anhydrous compound is little influenced from the atmosphere used. On the other hand, the mechanisms of thermal decomposition are profoundly influenced by the atmosphere used, as can also be observed in the EGA data. In addition, a comparison between two calorimetric techniques, Microwave Thermal Analysis (MWTA) and DSC, was made which showed similar profiles. Two evolved gas analysis (EGA) techniques: TG-DSC coupled to FTIR and HSM coupled to a quadrupole mass spectrometer (MS) were also used to provide additional information about the pyrolysis mechanism.